Biological interaction of thiamine with lysozyme using binding capacity concept and molecular docking. Issue 10 (2nd October 2016) - Hosseinzadeh, Reza; Khorsandi, Khatereh; Sheikh-Hasani, Vahid; Khatibi, Ali
Abstract : The binding of thiamine (vitamin B1 ) on lysozyme has been examined at various ionic strengths of phosphate buffer (pH 6.9), various pH values, and various protein concentrations at 25°C using thiamine selective membrane electrode. This method is faster and more precise than equilibrium dialysis technique which can obtain sufficient and accurate data for binding analysis. The values of Hill equation parameters were estimated for each set using binding capacity concept and used for calculation of intrinsic binding affinity. The results represent two binding sets for thiamine on lysozyme at various experimental conditions.